Development of Applications Media Interactive Based on Articulate Storyline 3 for Early Reading - Siti Latifa Zahara; Heri Suwignyo; Shirly Rizki Kusumaningrum (Syntax Corporation Indonesia, 2023)
The rapid development of technology can have a positive influence on the learning process. Technology support in learning can be a means in the learning process. The existence of technology can be an instructional scaffold, namely as a form of teacher support to students during the learning process. The purpose of this research is to develop a product in the form of an interactive media application based on articulate storyline for initial reading. This developed product is used by students at the stage of learning to read. The research method used in this study is using 4D research methods. Starting from the define (discovery), design (design), develop (development), and dessiminate (deployment) stages. This product that has been developed has gone through the validation stage, namely validation by media experts and validation by learning content experts (material). The results of validation by media experts of 91% and the results of validation by learning content experts (material) of 93% which shows that this interactive media application is very feasible to use.